2017
DOI: 10.4103/ejd.ejd_357_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge among general dentists in treatment of traumatic injuries in primary teeth: A cross-sectional questionnaire study

Abstract: Objective:The purpose of the present study was to assess the knowledge of General dentist regarding the management of dental traumatic injuries of primary teeth.Materials and Methods:A total of 100 general dentists were selected and a validated questionnaire was distributed among the dentist to assess their knowledge on treatment strategies regarding traumatized primary teeth.Statistical Analysis:Data were entered into SPSS version 20.0 for percentages. The correct answers were tested in relation to the dentis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
3
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(137 citation statements)
references
References 14 publications
5
125
3
4
Order By: Relevance
“…Nevertheless, studies have shown the lack of information and knowhow in dental trauma emergency care of teachers, athletes, rescue staff, paramedics, educators, sportive coaches, physicians, nurses, and dental professionals. [ 9 10 ] These findings characterize an alarming situation that might lead to irreversible damages to the affected tooth that did not receive the appropriate treatment in the local of the accident. [ 7 8 9 10 ] In addition, health professionals might be frequently requested to help in accidents involving tooth injury, so they might know the emergency procedures to save traumatized teeth preventing posttraumatic complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies have shown the lack of information and knowhow in dental trauma emergency care of teachers, athletes, rescue staff, paramedics, educators, sportive coaches, physicians, nurses, and dental professionals. [ 9 10 ] These findings characterize an alarming situation that might lead to irreversible damages to the affected tooth that did not receive the appropriate treatment in the local of the accident. [ 7 8 9 10 ] In addition, health professionals might be frequently requested to help in accidents involving tooth injury, so they might know the emergency procedures to save traumatized teeth preventing posttraumatic complications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 10 ] These findings characterize an alarming situation that might lead to irreversible damages to the affected tooth that did not receive the appropriate treatment in the local of the accident. [ 7 8 9 10 ] In addition, health professionals might be frequently requested to help in accidents involving tooth injury, so they might know the emergency procedures to save traumatized teeth preventing posttraumatic complications. Thinking in this way, it is important to start teaching dental trauma emergency protocols to undergraduate health students so that they can be prepared to act when this situation happens.…”
Section: Introductionmentioning
confidence: 99%
“…Preservation of primary teeth in the dental arch is important for optimal position of permanent teeth. Grossly decayed primary teeth which are extracted before exfoliation causes space in the dental arch which causes malocclusion if space maintainer was not given (Ravikumar et al, 2017;Panchal et al, 2019). Bacteria play a vital role in the initiation and progression of pulpal and periodontal disease (Jeevanandan, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It has a multifactorial aetiology which leads to initiation and progression of a lesion. Early childhood caries is one arising prevalent disease which can be a cause of premature loss of primary teeth (Ravikumar et al, 2017;Subramanyam, 2018) Pulpectomy procedure is performed in primary teeth to avoid extraction and to maintain its form and function (Govindaraju et al, 2017b,a,c) Fluoride is known to prevent caries by deposition of calcium luoride crystals (Jeevanandan, 2017;Jeevanandan and Govindaraju, 2018) which is more resistant to demineralisation (Nair, 2018;Panchal, 2019) of the tooth (Somasundaram, 2015;Ramakrishnan, 2017) Dental age estimation is based upon the rate of the development and calci ication of the tooth buds and the progressive sequence of their emission within the oral cavity (Sachan et al, 2013) Dental age is of speci ic intrigued to the pediatric dental practitioner and the orthodontist in arranging the treatment of distinctive sorts of malocclusion in connection to maxillofacial growth (Demirjian et al, 1973).…”
Section: Introductionmentioning
confidence: 99%